2016
DOI: 10.1002/jcc.24289
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory of the CuA‐like Cu2S2 diamond core in Cu (NGuaS)2Cl2

Abstract: Density functional theory (DFT) calculations with localized as well as plane-wave basis functions are performed for the recently reported dicopper thiolate species Cu2 (NGuaS)2 Cl2 [NGuaS = 2-(1,1,3,3-tetramethylguanidino) benzenethiolate, C11 H16 N3 S] and its bromo derivative [Neuba et al., Angew. Chem. Int. Ed. 2012, 51, 1714.]. For both hybrid and semilocal functionals, the neutral complexes are found to have broken symmetry (BS) character, with electron paramagnetic resonance silent, antiferromagnetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 119 publications
(178 reference statements)
0
26
0
Order By: Relevance
“…Formally one would assign two of the Cu ions an oxidation state of +II and the remaining four +I. This might lead to the assumption that an antisymmetric spin coupling emerges which has to be treated by an open shell BS wave function as proposed by Noodleman as it is already found in the related Cu 2 S 2 diamond core . The study of the dinuclear copper core shows that the minimum wave function is described by a BS wave function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Formally one would assign two of the Cu ions an oxidation state of +II and the remaining four +I. This might lead to the assumption that an antisymmetric spin coupling emerges which has to be treated by an open shell BS wave function as proposed by Noodleman as it is already found in the related Cu 2 S 2 diamond core . The study of the dinuclear copper core shows that the minimum wave function is described by a BS wave function.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that it reproduces accurate densities which is important as we perform detailed bonding and transition analyses . The inclusion of dispersion interaction is particularly vital for the determination of the correct structure in gas phase . The dispersion forces are modeled here using the post‐scf method by Grimme with the Becke and Johnson damping .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are still ongoing controversial discussions on whether there are Cu(I) or Cu(II) species arising and which role the nitric oxide plays in terms of oxidation states, DFT calculations and an EPR measurement of the adduct of [Cu(btmgp)Br] and NO were performed. First, a geometrical optimization was performed with the hybrid meta GGA functional TPSSh and the def2‐TZVP basis set, which proved excellent in our working group for several different cases . The Cu atom is coordinated by the two N atoms, the bromide ion, and the NO ligand in a distorted tetrahedral fashion.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] In order to understand the mechanism of their function, orbital structures of many copper enzymes and their model complexes were analysed both experimentally and theoretically. [15][16][17][18] Charge transfer that occurs during the catalytic cycle of a copper enzyme can be modelled by optical excitation of the metal-to-ligand or ligand-to-metal charge transfer states in a mimetic copper complex. Structural changes that accompany such photoinduced charge transfer typically occur on nanosecond timescales or faster and can thus be monitored almost exclusively by pump-probe time-resolved techniques.…”
Section: Introductionmentioning
confidence: 99%